2013
DOI: 10.1128/aac.00315-13
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir Plasma Concentrations and Virological Outcome with Lopinavir-Ritonavir Monotherapy in HIV-1-Infected Patients

Abstract: There is significant intra-and intersubject variability in lopinavir (LPV) plasma concentrations after standard dosing; thus, this prospective study was conducted to determine whether low plasma LPV concentrations could be associated with virological outcome throughout lopinavir-ritonavir maintenance monotherapy (mtLPVr) in the clinical practice setting. If this hypothesis would be confirmed, LPV drug monitoring could improve the efficacy of mtLPVr regimens. Patients with previous virological failure (VF) on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…We were unable to analyse adherence as a predictor of VF because the inclusion and exclusion criteria of the study led to the selection of a very therapy-adherent study population: no history of VF on any previous cART regimen, self-reported adherence during DTG monotherapy > 95%, and therapeutic DTG plasma concentrations in all patients with and without VF. DTG plasma concentrations were adequate in both groups, and there was no significant difference in DTG plasma concentration between patients with and without VF, which is consistent with previous studies which did not identify lower PI plasma concentrations as a risk factor for VF in patients receiving PI monotherapy [16,17]. It must be noted that drug level measurement was only performed at single time-points, so the possibility of temporary nonadherence between study visits cannot be ruled out.…”
Section: Discussionsupporting
confidence: 88%
“…We were unable to analyse adherence as a predictor of VF because the inclusion and exclusion criteria of the study led to the selection of a very therapy-adherent study population: no history of VF on any previous cART regimen, self-reported adherence during DTG monotherapy > 95%, and therapeutic DTG plasma concentrations in all patients with and without VF. DTG plasma concentrations were adequate in both groups, and there was no significant difference in DTG plasma concentration between patients with and without VF, which is consistent with previous studies which did not identify lower PI plasma concentrations as a risk factor for VF in patients receiving PI monotherapy [16,17]. It must be noted that drug level measurement was only performed at single time-points, so the possibility of temporary nonadherence between study visits cannot be ruled out.…”
Section: Discussionsupporting
confidence: 88%
“…1B and Table 1). HIV-1 patients treated with 400 mg of lopinavir and 100 mg of ritonavir twice daily may reach the minimal lopinavir serum concentration at 9.4 μM (IQR 7.2-12.1 μM), which is below the EC 50 against SARS-CoV-2 virus in vitro (Lopez-Cortes et al, 2013). Currently, lopinavir/ritonavir at 400mg/100 mg twice daily with or without ribavirin are part of the recommended treatment for managing COVID-19 patients in China (China National Health Commission, 2020).…”
mentioning
confidence: 91%
“…It is important to note that the IC 50 of the inhibitors were in the micromolar range, which is not considered optimal for the inhibition of the viral enzyme. Previous studies have reported that the minimum concentrations (C min ) for lopinavir, darunavir, saquinavir, and atazanavir in patient's serum under antiretroviral treatment was found to be 9.3, 3.3, 3.8, and < 1 µM, respectively [29][30][31][32]. It would indeed be challenging to achieve such high plasma levels of the inhibitors in order to block the viral replication, moreover, the cytotoxic effects of some of the inhibitors, in addition to the side effects commonly observed with PIs questions the use of anti-HIV PIs in the context of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%